Vitreous Hemorrhage in Pediatric Age Group - Dora H. AlHarkan; Eman S. Kahtani; Priscilla W. Gikandi; Ahmed M. Abu El-Asrar (Journal of Ophthalmology)
Purpose. To identify and study causes of vitreous hemorrhage (VH) in pediatric age group and to investigate factors predicting visual and anatomical outcomes. Procedure. A retrospective review of patients aged 16 years or less with the diagnosis of vitreous hemorrhage from January 2005 until December 2010. Results. A total number of 230 patients (240 eyes) were identified. Traumatic vitreous hemorrhage accounted for 82.5%. In cases of accidental trauma, final visual acuity of 20/200 was significantly associated with visual acuity of ≥20/200 at presentation and the absence of retinal detachment at last follow-up. Patients with nontraumatic vitreous hemorrhage were significantly younger with higher rates of enucleation/evisceration/exenteration and retinal detachment at last follow-up compared to traumatic cases. Conclusion. Trauma is the most common cause of VH in pediatric age group. In this group, initial visual acuity was the most important predictor for visual outcome, and the presence of retinal detachment is a negative predictor for final good visual outcome. The outcome is significantly worse in nontraumatic cases compared to traumatic cases.